Online assessment of the perception of loneliness and associated factors in Colombian climacteric women during the COVID-19 pandemic: A cross-sectional study (2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has generated changes due to confinement, this measure can increase the perception of loneliness. The objective was to estimate the frequencies of emotional, social and general loneliness and their association with fear and anxiety with COVID-19, religiosity and severe deterioration of quality of life in middleaged women. Methods: A cross-sectional study in Colombian women (40-59 y, n=984) surveyed with an electronic form that included sociodemographic characteristics and validated measures (Menopause Rating Scale, de Jong Gierveld Loneliness Scale, fear of COVID-19 scale, Coronavirus Anxiety Scale and Francis Scale for Religiosity). Associations of emotional, social and general loneliness (dependent variables) with severe somatic, psychological, urogenital and quality of life deterioration, as well as with high religiosity, anxiety and high fear of COVID-19 (independent variables), were estimated. Results: The median age was 47 years old, and 39.2% [95% CI: 36.2-42.3] postmenopausal. Severe deterioration in somatic, psychological, urogenital domains and quality of life in women with emotional, social and general loneliness was found (P < 0.001). In adjusted models, high fear of COVID-19, severe deterioration of psychological and urogenital domains and quality of life were associated with emotional, social and general loneliness. Anxiety with COVID-19, somatic domain and high religiosity were not associated with loneliness. Conclusion: Emotional, social and general loneliness were identified in 4/10 middle-aged Colombian women surveyed, and the associated factors were high fear of COVID-19, severe deterioration of quality of life and psychological and urogenital domains. Professionals who care for climacteric women should explore the perception of loneliness when assessing menopausal symptoms